META-ANALISIS PENGARUH MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Tumangkeng, Yenti Winataria; Yusmin, Edy; Hartoyo, Agung (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis meta-analysis aims to determine influence of the use of instructional media to students' mathematics learning outcomes. The type of this research is descriptive research survey. By purposive sampling techniques, 31 thesis of mathematics education student of FKIP Untan in the period 2009-2016 are summarized. The calculation results show that total effect size is 0,95 (SD = 0,79). This means use of instructional media gives result of 32,89% for improving students' mathematics learning outcomes. Type of instructional media that gives largest effect size is printed media ( = 1,13, SD = 1,10) with the amounts of 37,08%. Based on the relationship between variables, it is known the use of instructional media that produces the largest effect size is applied to matter numbers ( = 1,44, SD = 0,58). Type of instructional media classification which have a major effect on the number matter are manipulative object media ( = 1,42, SD = 0,47). While based on the level of school, the use of instructional media that produces the largest effect size is applied at elementary school ( = 1,54, SD = 0,62). Keywords: meta-analysis, effect size, instructional media, mathematic education